Aldehyde Dehydrogenase Inhibitors for Cancer Therapeutics. (October 2019) - Dinavahi, Saketh S.; Bazewicz, Christopher G.; Gowda, Raghavendra; Robertson, Gavin P.
Abstract : Aldehyde dehydrogenases (ALDHs) are highly expressed in the chemotherapy- and radiotherapy-resistant cell subpopulations of many different cancer types. Accordingly, the development of ALDH inhibitors may be the most direct approach to target these cell populations. However, inhibiting multiple ALDH family members can be toxic and isoform-specific inhibition is often ineffective. This review discusses the role of ALDH in cancer and therapy resistance, and then overviews the various available ALDH inhibitors with a focus on the clinical potential and limitations of these agents as cancer therapeutics. Finally, challenges and future research directions to effectively target ALDH in the management of cancer therapy resistance are discussed. Highlights: Aldehyde dehydrogenase (ALDH) overexpression is associated with cancer progression and therapy resistance. ALDH activity in cells is generally a combination of the activities of multiple ALDH isoforms. Targeting ALDHs is likely the most direct approach to inhibiting therapy-resistant ALDH-overexpressing cells, but inhibiting multiple ALDH family members can be toxic, and isoform-specific inhibition is often ineffective, which has limited the use of these agents. Despite the recent development of numerous ALDH inhibitors as anticancer agents, research focused on developing efficacious, non-toxic ALDH inhibitors is still needed.